KOMUNIKASI NONVERBAL PRAKTISI SENI BELADIRI AIKIDO (Studi Fenomenologis Praktisi Aikido di Perguruan Aikido Nonafiliasi Bandung Aiki Jutsu) - Sukmayadi, Vidi Sukmayadi (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
Aikido as a form of martial arts has its own unique characteristics both in term of tradition and communication behavior that applied by its students. The study is aimed to analyze the practitioners’ nonverbal communication behaviors in Bandung Aiki Jutsu nonaffiliated Aikido school. The study focused on three matters related to the communication phenomena, and they are; nonverbal communication pattern, meanings of nonverbal symbols comprehended by the practitioners, and the practitioners’ social construction as well as the school. The author employed a qualitative approach in the tradition of phenomenology. Then, in collecting the data, the author employed an emic approach in order to have an in-depth interview and a participation observation. Besides, documentation study is used to support the data findings. The result of the study shown that there are two motives that appear behind the practitioners interest toward Bandung Aiki Jutsu Aikido school, they are internal aikidoka motive and external aikidoka motive. Besides, the study pointed out that the nonverbal symbols in the Aikido school are apreciated by the Aikido practitioners as symbols of self harmony, respect, motivation, togetherness, self identity, self confidence, and responsibility The applied nonverbal symbols is a form of appreciation and acculturation towards Japanese culture. Therefore, the Japanese culture can be synchronized to local culture that has been obtained by the Aikido practitioners in Bandung Aiki Jutsu. Moreover, the nonverbal symbols that applied by the Aikido practitioners appear to have subsitution, complementary, and accentualization function.Key words: Aikido, Bandung Aiki Jutsu, Nonverbal Communication